A Novel on Stability and Fault Ride through Analysis of Type-4 Wind Generation System Integrated to VSC-HVDC Link - Ch. S. V. S. Phani Kumar; T. Vinay Kumar (International Journal of Applied Power Engineering (IJAPE), 2018)
Now-a-days pollution is increasing due to “Non Renewable Energy Sources”. In order to enhance the efficiency of conventional grid and to generate the electrical power in eco-friendly way, the renewable energy sources are employed. In this paper a type 4 wind generation system is implemented to analyse the system under fault conditions and to analyse the grid stability. In the proposed system type-4 wind generation system integrated to grid through VSC-HVDC link analysis is done by considering a fault on the grid side by the system gets isolated and wind generation system transfers voltage to local load and remote load. When a DC fault is occurred on the VSC-HVDC link then the grid side breaker and wind side breaker gets open, then system gets isolated. This is implemented by considering “Low Voltage Ride Through” (LVRT) conditions, According to the Indian grid code of contact wind generation maintain constant even the voltage collapse is occurred on the grid side. The proposed VSC-HVDC based Type-4 Wind Generation System give more reliable to operate in LVRT condition and can meet the Load demand when the system is under fault condition to some extent; The proposed method is Type –4 Wind generator is of 4.4MW/2.2kV each with a total plant capacity of 110MW operated with VSC based HVDC transmission system with 110kV DC bus voltage connected to 220kV grid. The results obtained shows the Grid is operates under fault ride through conditions stability.